(untitled) (Research, Society and Development, 2023)
Parkinson’s disease (PD) is an idiopathic neurodegenerative disease, and it has been linked to long-term pesticide exposure. In this study, we aimed to determine whether pesticide exposure was associated with the risk of PD and other neurological manifestations. We conducted a pilot case-control study in patients from two neurology outpatient clinics. PD cases (n = 29) were matched with controls (n = 83) randomly selected from the same outpatient clinics. For data collection, telephone-based interviews were performed using a structured questionnaire. Overall, PD cases were proportionally more exposed to pesticides than the control group, but the association was not statistically significant (OR= 1.92; 95%, CI: 0.77–4.66; p = 0.15). We identified a high prevalence of neurological and psychological symptoms among the study participants, especially among the individuals who reported pesticide exposure. Our results reinforce the importance of further studies investigating the relationship between PD and pesticides to better understand this phenomenon.